Klasifikasi Pola Frasa Ajektival Bahasa Teon: Classification of Teon Language Ajectival Phrase Patterns - Erniati, Erniati; Mudarsep, Mudarsep (Balai Bahasa Provinsi Papua, 2022)
This study aims to conserve the system of adjective phrases in the Teon language spoken by people in four countries, namely Watludan, Yafila, and Issu Villages, in Central Maluku District. Data was collected through an instrument containing examples of Indonesian phrases and then translated into Teon language according to data needs. Data analysis was carried out by classifying all types of phrases according to the Teon language. After the data is classified, it is continued by studying based on the type of nominal phrase by making a formula according to the phrase patterns of the Teon language. The results showed that the adjective phrases in Teon's language were divided into two, namely attributive endocentric nominal phrases and coordinating endocentric nominal phrases. Attributive endocentric adjective phrases consist of several types of phrases based on their attribute word classes, namely (1) adjective phrases with positive comparison level adverbial attributes; (2) adjective phrases with comparative adjective attributes; (3) adjective phrases with the attributes of nagator/denial adverbial adjectives; (4) adjective phrases with excessive adverbial attributes; (5) adjective phrases with relative adverbial attributes. (2) the coordinating endocentric adjective phrases are divided into two, namely the addition and selection coordinating endocentric adjective phrases.